The reality of embezzlement and bribery crimes in the banking sector in light of Law 06/01, amended and supplemented - Bouokka, Kamla (The International tax journal, 2025)
The Algerian legislator has clearly emphasised the importance of embezzlement and bribery crimes in the context of offences undermining the duties of public office. These crimes are among the most dangerous types of administrative corruption afflicting the state, representing a breach of trust. This highlights the importance of implementing preventive measures against internal and external corruption. Algeria has aligned its efforts with those of the international community, keeping pace with the transformations mandated by international relations. Amending its domestic legislation to comply with these obligations was imperative for Algeria, especially given the Penal Code’s and related laws’ inability to combat corruption and develop the national legislative framework. This was achieved through the enactment of Law 06/01, dated 20 February 2006, concerning the prevention and combating of corruption, which was amended and supplemented in 2011. The law aims to support measures to prevent and combat corruption, and enhance integrity, accountability and transparency in the management of the public and private sectors.